2014
DOI: 10.1111/jpr.12061
|View full text |Cite
|
Sign up to set email alerts
|

Perceived group identity of outgroup members and anticipated rejection: People think that strongly identified group members reject non‐group members

Abstract: Many studies of intergroup relations have examined the effects of group identity on various types of intergroup cognition and behavior. However, few studies have focused on the perceived group identity of outgroup members. This study examined the effects of perceptions of outgroup identity on anticipated rejection by an outgroup. In Study 1, we administered a questionnaire pertaining to 30 social groups to Japanese undergraduate and vocational students. The collective images and intra-individual processes rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We make similar arguments for our theoretical underpinnings, as although we apply prejudice-distribution theory to the US setting, the underlying dynamics and subsequent outcomes are applicable in other contexts (e.g. Nawata and Yamaguchi, 2014). Finally, using MTurk to collect the data offers a number of potential benefits (Buhrmester et al, 2011;Casler et al, 2013;Landers and Behrend, 2015), but there are also potential limitations, including not being able to assess a response rate.…”
mentioning
confidence: 87%
“…We make similar arguments for our theoretical underpinnings, as although we apply prejudice-distribution theory to the US setting, the underlying dynamics and subsequent outcomes are applicable in other contexts (e.g. Nawata and Yamaguchi, 2014). Finally, using MTurk to collect the data offers a number of potential benefits (Buhrmester et al, 2011;Casler et al, 2013;Landers and Behrend, 2015), but there are also potential limitations, including not being able to assess a response rate.…”
mentioning
confidence: 87%
“…Moreover, because observers tend to believe that people who are more identified with their group will be more likely to act in ways that favor their group (Nawata & Yamaguchi, 2014), they may be more likely to conclude that a negative label is less negative after observing an individual willingly self-label with it. Work by Galinsky et al (2013) supports this line of theorizing.…”
Section: Hypothesis 3amentioning
confidence: 99%
“…On one hand, self-labeling arising from increased group identification could lessen conflict between groups, because the stigma is reduced and legitimization of the stigmatized group increased (Creed & Scully, 2000;Hampel & Tracey, 2016). Conversely, as self-labeling causes observers to see the self-labeler as more identified with their group, intergroup conflict may actually be increased (Nawata & Yamaguchi, 2014). Work by Kaiser and Pratt-Hyatt (2009) found that Whites expressed more negative attitudes toward racial minorities who were strongly identified (vs. weakly identified) with their group (see also Major, Quinton, & McCoy, 2002;Sellers & Shelton, 2003).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Negative stimuli can lead to temporal underestimation (e.g., Angrilli et al 1997) so tendencies to show negative attitudes towards an out-group (e.g., Nawata and Yamaguchi 2014) should lead to temporal underestimation for out-group movements (relative to in-group). We also expected to detect a negative correlation between IAT scores, which provide a measure of implicit racial bias of participants, and the time estimation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Given the link between embodiment to social group representation (e.g., Maister et al 2013 ; Peck et al 2013 ), as well as evidence that the temporal estimation of body movements is influenced by embodiment (Nather et al 2011 ; Avanzino et al 2013 ; Vicario et al 2017 ), we predict that participants will differently estimate the completion time of in-group and out-group writing movements. Negative stimuli can lead to temporal underestimation (e.g., Angrilli et al 1997 ) so tendencies to show negative attitudes towards an out-group (e.g., Nawata and Yamaguchi 2014 ) should lead to temporal underestimation for out-group movements (relative to in-group). We also expected to detect a negative correlation between IAT scores, which provide a measure of implicit racial bias of participants, and the time estimation performance.…”
Section: Introductionmentioning
confidence: 99%